Multiband counterparts of two eclipsing ultraluminous X-ray sources in M 51. Issue 3 (9th January 2018) - Urquhart, R; Soria, R; Johnston, H M; Pakull, M W; Motch, C; Schwope, A; Miller-Jones, J C A; Anderson, G E
Abstract: We present the discovery and interpretation of ionized nebulae around two ultraluminous X-ray sources in M 51; both sources share the rare property of showing X-ray eclipses by their companion stars and are therefore prime targets for follow-up studies. Using archival Hubble Space Telescope images, we found an elongated, 100-pc-long emission-line structure associated with one X-ray source (CXOM51 J132940.0+471237; ULX-1 for simplicity), and a more circular, ionized nebula at the location of the second source (CXOM51 J132939.5+471244; ULX-2 for simplicity). We observed both nebulae with the Large Binocular Telescope's Multi-Object Double Spectrograph. From our analysis of the optical spectra, we argue that the gas in the ULX-1 bubble is shock-ionized, consistent with the effect of a jet with a kinetic power of ≈2 × 10 39 erg s −1 . Additional X-ray photoionization may also be present, to explain the strength of high-ionization lines such as He ii λ4686 and [Ne v ] λ3426. On the other hand, the emission lines from the ULX-2 bubble are typical for photoionization by normal O stars suggesting that the nebula is actually an H ii region not physically related to the ULX but is simply a chance alignment. From archival Very Large Array data, we also detect spatially extended, steep-spectrum radio emission at the location of the ULX-1 bubble (consistent with its jet origin), but no radio counterpart for ULX-2 (consistent with the lack of shock-ionized gas around that source).